Workload and associated factors: a study in maritime port in Brazil - Marta Regina Cezar-Vaz; Clarice Alves Bonow; Marlise Capa Verde de Almeida; Cynthia Fontella Sant'Anna; Leticia Silveira Cardoso
ABSTRACT Objective: to identify the effect of the mental, physical, temporal, performance, total effort and frustration demands in the overall workload, and in the same way analyze the global burden of port labor and associated factors that contribute most to their decrease or increase. Method: a cross-sectional, quantitative study, developed with 232 dock workers. For data collection, a structured questionnaire with descriptive, occupational, smoking and illicit drug use variables was applied, as well as variables on the load on the tasks undertaken at work, based on the questionnaire NASA Task Load Index. For data analysis, we used the analysis of the Poisson regression model. Results: the demands physical demand and total effort showed greater effect on the overall workload, indicating high overall load on port work (134 employees - 58.8%). The following remained associated statistically with high levels of workload: age (p = 0.044), to be employee of the wharfage (p = 0.006), work only at night (p = 0.025), smoking (p = 0.037) and use of illegal drugs (p = 0.029). Conclusion: the workload in this type of activity was high, and the professional category and work shift the factors that contributed to the increase, while the age proved to be a factor associated with a decrease.